Antiapoptotic Bcl‐2 homolog CED‐9 in Caenorhabditis elegans: Dynamics of BH3 and CED‐4 binding regions and comparison with mammalian antiapoptotic Bcl‐2 proteins. Issue 6 (23rd November 2013) - Modi, Vivek; Sankararamakrishnan, Ramasubbu
ABSTRACT Proteins belonging to Bcl‐2 family regulate intrinsic cell death pathway. Although mammalian antiapoptotic Bcl‐2 members interact with multiple proapoptotic proteins, the Caenorhabditis elegans Bcl‐2 homolog CED‐9 is known to have only two proapoptotic partners. The BH3‐motif of proapoptotic proteins bind to the hydrophobic groove of prosurvival proteins formed by the Bcl‐2 helical fold. CED‐9 is also known to interact with CED‐4, a homolog of the human cell death activator Apaf1. We have performed molecular dynamics simulations of CED‐9 in two forms and compared the results with those of mammalian counterparts Bcl‐XL, Bcl‐w, and Bcl‐2. Our studies demonstrate that the region forming the hydrophobic cleft is more flexible compared with the CED‐4‐binding region, and this is generally true for all antiapoptotic Bcl‐2 proteins studied. CED‐9 is the most stable protein during simulations and its hydrophobic pocket is relatively rigid explaining the absence of functional redundancy in CED‐9. The BH3‐binding region of Bcl‐2 is less flexible among the mammalian proteins and this lends support to the studies that Bcl‐2 binds to less number of BH3 peptides with high affinity. The C‐terminal helix of CED‐9 lost its helical character because of a large number of charged residues. We speculate that this region probably plays a role in intracellular localization of CED‐9. The BH4‐motif accessibility in CED‐9 and Bcl‐w is controlled by the loop connecting the first two helices. Although CED‐9 adopts the same Bcl‐2 fold, our studies highlight important differences in the dynamic behavior of CED‐9 and mammalian antiapoptotic homologs. Proteins 2014; 82:1035–1047. © 2013 Wiley Periodicals, Inc.